## UmarsBack 2 years ago Help, explain step by step.

1. UmarsBack

Solve: 3(x + 4) - 4(x + 3) = 7x + 16.

2. Khaleesi

distribute the 3 and the -4 into the parentheses. what do you get?

3. UmarsBack

3x+12 - 4x + (-12) = 7x +16

4. Khaleesi

you can make that + (-12) just -12. so 3x + 12 - 4x - 12 = 7x + 16 now you gotta combine your like terms

5. UmarsBack

x = 7x + 16?

6. Khaleesi

3 - 4 = -1, so your x should be negative -x = 7x + 16 now you have to move the 7x to the left side

7. UmarsBack

6x = 16 /6 /6 x=3 ?

8. Khaleesi

no. we have to do the opposite to both sides when moving the 7x to the other side. the opposite of 7x is -7x. so subtract 7x from both sides

9. UmarsBack

7x = 16 -7x -7x

10. Khaleesi

no :/ since we have -x on the left side, we have to do -1x - 7x, which is -8x. so -8x = 16 now you can divide both sides by -8 to solve for x

11. UmarsBack

Ohh sorry, i get confused when it comes to integers! -8x = 16 -8x -8x x=-2

12. Khaleesi

that's right! :D

13. UmarsBack

Thank you for helping me!

14. Khaleesi

no problem :]

Find more explanations on OpenStudy